Plagiarism and fabrication: dishonesty in the newsroom : a thesis presented in partial fulfilment of the requirements of the degree of Master of Management (Communication) at Massey University, Wellington, New Zealand - Samson, Alan Michael (Massey University, 2009)
This first comprehensive study of New Zealand news media plagiarism proceeds from the observation that plagiarism, if not demonstrably increasing, is more common than many practitioners would care to believe. It affirms that, contrary to conventional opinion, plagiarism cannot be understood or dismissed simply or entirely as the product of dishonest or lazy journalists. The study findings support indications of an underlying culture of copying within news media organisations—a professional ideology encouraging, if not overtly justifying, copying, and discouraging clear authorship attribution. The findings emanate from responses to a survey distributed to all New Zealand’s journalists, followed by in-depth interviews with five journalists identified as having personal experience with aspects of the practice identified in the survey, and a sixth with a journalist against whom a complaint of plagiarism was upheld by watchdog body, the NZ Press Council. The research analysed the just four complaints related to plagiarism brought before the Press Council since its 1972 inception, as well as another five much-publicised examples of the practice written about in the news media, to the present day. Of the nine cases examined, three reflected the most serious type of dishonesty associated with Jayson Blair of the New York Times—calculated theft of words as well as outright interview fabrication. The others can be categorised in a perceived less blameworthy variety of plagiarism, bedevilled by confusion of terms and newsroom pressures. But because much run-of-the-mill plagiarism is likely to have gone unrecorded and unnoticed beyond the newsroom involved, the true extent of any sort of plagiarism here could not be judged. What was possible in this research, was to gauge a sense of prevalence by asking working journalists not of their own sins, but of their experience of being plagiarised by others. Suddenly the numbers of plagiarism cases rocketed, not in a usefully quantifiable way, but clearly demonstrative of an extent sufficient to warrant analysis of nature and origin. These experiences were set against an American model that identified four antecedents of plagiarism behaviour, two individual—journalistic rationalising of dishonesty and problematic techniques—and two situational—definitional ambiguity and reporter aversion to attribution. What became clear in these analyses was that, though all news media organisations view plagiarism very seriously, few if any acknowledge their own role in perpetrating the practice, that journalism is an industry that proceeds from an ideology of matching and copying.
Keywords: News media; New Zealand journalists; Fields of Research::350000 Commerce, Management, Tourism and Services::359900 Other Commerce, Management, Tourism and Services